Steroid-eluting stents in patients with acute coronary syndrome: the Dexamethasone Eluting Stent Italian REgistry. Issue 5 (27th September 2006) - Ribichini, Flavio; Tomai, Fabrizio; Paloscia, Leonardo; Di Sciascio, Germano; Carosio, Giuseppe; Romano, Michele; Verna, Edoardo; Galli, Mario; Tamburino, Corrado; De Cesare, Nicoletta; Pirisi, Raimondo; Piscione, Federico; et al.
Abstract : Objective: To assess immediate and mid-term clinical and angiographic outcomes of the dexamethasone drug-eluting stent (D-DES) in patients with acute coronary syndrome (ACS). Patients and methods: A prospective, nationwide, controlled, registry. Inflammation plays a key role in ACS, and the anti-inflammatory effects of local elution of dexamethasone in unstable plaques may represent a valid therapeutic approach. All patients had ACS on admission (n = 332). 81.5% of the patients had unstable angina and 18.5% had non-ST elevation myocardial infarction (MI). 47% had ST-T segment changes, 59% had troponin elevation, 77% had elevated C-reactive protein levels and 48% had intermediate–high Thrombolysis in Myocardial Infarction risk score. Patients were treated according to an early invasive approach with 420 D-DES in 387 coronary lesions. Primary end point was the cumulative incidence of death, MI and ischaemia-driven target vessel revascularisation (TVR) at 6 months. Results: At 30 days, 2 (0.6%) patients died, and sub-acute stent thrombosis occurred in 2 patients. At 6 months, 328 (98.8%) patients were controlled, 3 (0.9%) patients had died, 7 (2.1%) had MI and 28 (8.5%) underwent ischaemia-driven TVR. Therefore, the primary end point occurred in 11.5% of patients. At multivariate analysis, multi-vessel coronary artery disease (odds ratio (OR) = 2.16, 95% CI = 1.47 to 3.17, p = 0.0001) and vessel diameter ⩽2.75 mm (OR = 1.64, 95% CI = 1.08 to 2.49, p = 0.02) were independent predictors of 6-month clinical events. Global angiographic restenosis rate was 33.3%. Conclusion: This is the first large, multicentre analysis of the clinical and angiographic outcomes obtained with D-DES implanted in ACS. D-DES offers a low rate of clinical events at 6 months, but has no anti-restenosis effect.